Formal synthesis of Cladospolide C & epi-Cladospolide C using R-(+)-γ-valerolactone as a chiral synthon. Issue 19 (10th May 2019) - Datrika, Rajender; Kallam, Srinivasa Reddy; Vidavalur, Siddaiah; Rajana, Nagaraju; Pratap, T.V.
Abstract: The formal synthesis of Cladospolide-C and its analog is achieved by using enantiopure ( R )-γ–valerolactone10 . The significant points of this synthesis are the stereoselective dihydroxylation of α, β -unsaturated ester16 using Sharpless protocol, Wittig olefination of γ –valerolactol6 with triphenylphosphonium iodide salt7, one pot selective oxidation of22 and subsequent C2-homologation with good E / Z ratio. Graphical abstract: Image 1